Conversion of Sunan Candlenut Oil to Aromatic Hydrocarbons with Hydrocracking Process Over Nano-HZSM-5 Catalyst - Al Muttaqii, Muhammad; Marbun, Maja Pranata; Sudibyo, Sudibyo; Aunillah, Asif; Pranowo, Dibyo; Hasanudin, Hasanudin; Rinaldi, Nino; Bardant, Teuku Beuna (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
In this paper, the catalysts (Nano-HZSM-5 and Fe-La/nano HZSM-5) were prepared with incipient wetness impregnation and applied for hydrocracking of Sunan candlenut oil. The hydrocracking process was conducted in a batch reactor with a pressure of 20-30 bar H2 gas for 2 h under various temperatures. The results demonstrated that hydrocracking of Sunan candlenut oil using nano HZSM-5 and Fe-La/NHZ catalysts could be converted into aromatic hydrocarbons, and the reaction temperature affected hydrocarbon production. The aromatic compounds, such as propyl-benzene, 1-ethyl-3-methylbenzene, heptyl-benzene, 2-ethyl-naphthalene, etc., reached 35.51% over the Fe-La/NHZ_2 catalyst. In all cases, the zeolite-based catalysts are the most suitable to produce aromatic hydrocarbons. Metal impregnated (Fe and La) on nano HZSM-5 catalyst could improve the aromatics compounds due to increased metal and acid sites. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).